Kodificirano albansko običajno pravo - Ibrahimi, Amir (Pravnik, 2016)
This article deals with the concept of the Albanian customary law, which is in the wider European legal science incorrectly equated solely with generalized record of the Albanian customary law in the form of The Kanun of Leke Dukagjini, although there are many other records showing a long and rich legal heritage of the Albanians. Primarily, the article explains the peculiar course and nature of partilineal transmission, ipso iure, of all decedent's assets left, property and legal relations of obligations and commitments, to the legal successors, within the institution of the traditional Albanian society. The focus is also on a comparison of the provisions of inheritance law set in the Albanian Kanun's with the Slovenian law and on the systematic presentation of individual inheritance institutes such as inheritance position of the decedents daughters, adopted children, illegitimate children, widows, virgjin (Albanian virgjëreshë or burrneshë), personal property of women (Albanian selem), succession without heirs, testamentary inheritance etc.
Keywords: Albania; Albanija; dedno pravo; dedovanje; Slovenia; Slovenija; Trusts and estates